A Development of Docking Phase Analysis Tool for Nanosatellite - Miri Jeong; Dong-Hyun Cho; Hae-Dong Kim (Journal of Astronomy and Space Sciences, 2020)
In order to avoid the high cost and high risk of demonstration mission of rendezvous-docking technology, missions using nanosatellites have recently been increasing. However, there are few successful mission cases due to many limitations of nanosatellites like small size, power limitation, and limited performances of sensor, thruster, and controller. To improve the probability of rendezvous-docking mission success using nanosatellite, a rendezvous-docking phase analysis tool for nanosatellites is developed. The tool serves to analyze the relative position and attitude control of the chaser satellite at the docking phase. In this tool, the Model Predictive Controller (MPC) is implemented as a controller, and Extended Kalman Filter (EKF) is adopted as a filter for noise filtering. To verify the performance and effectiveness of the developed tool for nanosatellites, simulation study was conducted. Consequently, we confirmed that this tool can be used for the analysis of relative position and attitude control for nanosatellites in the rendezvous-docking phase.